Percepção sobre restauro da mata ciliar realizado em propriedades rurais às margens do Ribeirão Feijão (Itirapina e São Carlos, SP) - Zattoni, Michelle (Universidade Federal de São Carlos, 2012)
This research aimed to survey the environmental perception of owners, employees and residents of rural properties in relation to the work of restoration of riparian vegetation. The data were collected through a structured interview script. The main result found was that respondents have relevant information about the importance of getting the reforestation to improve the quality of life and environment. However, there are difficulties in implementing conservation actions in the areas of permanent preservation in the properties, as well as lack of rural extension support. The conclusion is that a better understanding of the local environmental issues perceived by local social actors may support future actions of the governmental and nongovernmental organizations working in the region of this research.
Perception on riparian forest restoration in rural properties in the margins of the Ribeirão Feijão (Itirapina e São Carlos, SP)
Keywords: Agroecologia; Percepção ambiental; População rural; Área de preservação permanente (APP); Reflorestamento; Mata ciliar; Environmental perception; Rural population; Permanent preservation area; CIENCIAS AGRARIAS